Insights into the REY inventory of seep carbonates from the Northern Norwegian margin using geochemical screening - Schier, Katharina; Himmler, Tobias; Lepland, Aivo; Kraemer, Dennis; Schönenberger, Jasmin; Bau, Michael (Chemical Geology, 2020)
Rare earth element and yttrium (REY) systematics of authigenic seep carbonates can provide insights into the physico-chemical characteristics of seep systems and allow discrimination of carbonate precipitation under seawater- or porewater-dominated fluid regimes. However, care must be taken when interpreting their REY systematics, since seep carbonates comprise a mixture of detrital silicates and authigenic carbonate cement. Since concentrations of trace elements, including Rb, Zr, Th and REY, are considerably lower in the carbonate fraction than in the detrital silicate fraction, leaching of these trace elements from detrital components (particularly aluminosilicates) even during a rather “mild” sample decomposition approach with, for example, nitric acid (HNO3) can effectively mask the authigenic carbonate REY signal. To assess this effect, trace element concentrations were determined in seep carbonates and detrital sediments from two sites off the Norwegian margin (Lofoten-Vesterålen margin and Vestnesa Ridge). Seep carbonate samples included bulk crusts and nodules, and individual microfacies (microcrystalline aragonite and/or Mg-calcite cementing detrital sediment and void-filling fibrous aragonite cement) microdrilled from crusts. A screening procedure based on Rb, Zr, Th and REY reveals effective masking of the carbonate REY systematics by leaching of trace elements from even minute amounts (0.1–1%) of detrital components. The latter cause elevated trace element concentrations and flat shale-normalized REY patterns. They are prominent in the bulk crusts and nodules, and in microcrystalline carbonate cementing sediment microfacies, which makes these unsuitable as archives of the REY inventory of the carbonate-precipitating fluid even when digested with HNO3. Some void-filling cements, however, contain little detrital material and show REY signatures characterized by light REY-depletion in shale-normalized (subscript SN) patterns and small negative CeSN anomalies. Comparison of the seep carbonate REYSN ...